Rapid immunofluorescence microscopy for diagnosis of melioidosis. - Wuthiekanun, V; Desakorn, V; Wongsuvan, G; Amornchai, P; Cheng, A; Maharjan, B; Limmathurotsakul, D; Chierakul, W; White, N; Day, N; Peacock, S (2005)
An immunofluorescent (IF) method that detects Burkholderia pseudomallei in clinical specimens within 10 min was devised. The results of this rapid method and those of an existing IF method were prospectively compared with the culture results for 776 specimens from patients with suspected melioidosis. The sensitivities of both IF tests were 66%, and the specificities were 99.5 and 99.4%, respectively.